TRAINING ON FOOD PACKAGING FOR MSMEs SENDEN VILLAGE TRENGGALEK BY UNAIR TEAM & PARTNER UNIVERSITIES - Aminah, Nanik Siti; Kristanti, Alfinda Novi; Ramadhan, Rico; Hendradi, Rimuljo; Takaya, Yoshiaki; Khoso, Mir Hasan; Baharin, Siti Nor Atika; Abdjan, Muhammad Ikhlas (Universitas Airlangga, 2025)
The International Community Services program (ICS) at Universitas Airlangga, part of the Tri Dharma of the university focusing on community service, aims to enhance human resource capacities within communities. In 2024, the program targeted Senden Village, Kampak sub-District, Trenggalek District, East Java, Indonesia, to assist its MSMEs in overcoming packaging challenges that hinder market interest. Collaborating with domestic and international universities, including Universitas Mayjen Sungkono, SMBBMU University Larkana Pakistan, UiTM Negeri Sembilan Malaysia, UM Malaysia, and Meijo University Japan, the program provided intensive training on innovative and functional packaging techniques. This program was chosen and considered urgent because processed food products produced by local MSMEs are still sold in bulk and packaged haphazardly. Therefore, a touch of hygienic and